2015
DOI: 10.1007/s00345-015-1560-1
|View full text |Cite
|
Sign up to set email alerts
|

Do lower urinary tract symptoms predict cardiovascular diseases in older men? A systematic review and meta-analysis

Abstract: PurposeTo study the incidence of CVD in men at risk, with and without LUTS. MethodsWe searched all longitudinal studies describing the association between LUTS and CVD (mortality) in October 2013 and December 2014 using MEDLINE, EMBASE, and the Cochrane Library Central Register. PRISMA criteria were met.ResultsWe included five studies with 6027 men with LUTS and 18,993 men without LUTS in the meta-analyses, with a follow-up period varying from 5 to 17 years. Studies totalled 2780 CVD events. No clear associati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(18 citation statements)
references
References 24 publications
1
16
1
Order By: Relevance
“…Gacci et al revealed that moderate to severe LUTS in men is strongly related to an increase in the risk of major cardiovascular events [7]. In contrast, Bouwman et al reported that LUTS in men is not a predictor of cardiovascular events [37]. In the present study, cardiovascular risk factors such as age, body mass index, glucose and Framingham risk score showed significant relationships with IPSS.…”
Section: Discussioncontrasting
confidence: 40%
“…Gacci et al revealed that moderate to severe LUTS in men is strongly related to an increase in the risk of major cardiovascular events [7]. In contrast, Bouwman et al reported that LUTS in men is not a predictor of cardiovascular events [37]. In the present study, cardiovascular risk factors such as age, body mass index, glucose and Framingham risk score showed significant relationships with IPSS.…”
Section: Discussioncontrasting
confidence: 40%
“…Without these factors, even SRs with meta‐analyses could not show consistent conclusions. Although Gacci et al reported the significant association between those two disease entities, Bouwman et al reported no significant association between LUTS and CVD. Several studies suggested the possibility of BPH as an early manifestation of CVD risk rather than their direct cross‐sectional relationship between those two entities.…”
Section: Discussionmentioning
confidence: 99%
“…Rather, it is plausible to assume that CVD risks could aggravate the LUTS. There are several studies which support the latter direction by suggesting that c reactive protein, hyperlipidemia, and artheosclerosis could have a negative impact on LUTS . Moreover, there are few studies which show improvement of CVD risk by medication for LUTS, as well as medication for CVD improves LUTS.…”
Section: Discussionmentioning
confidence: 99%
“…Within three of the four clusters, the most prevalent chronic conditions, such as hypertension and hyperlipidaemia, are associated with increased CVD risk. There is increasing interest in the evaluation of how CVD may affect LUTS [31,32]. White matter hyperintensities in the CNS, which are associated with long-term CVD, are also associated with severity of UI in older adults [33].…”
Section: Discussionmentioning
confidence: 99%